2013
DOI: 10.1007/s10482-013-0047-6
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing aquatic bacteria by light and transmission electron microscopy

Abstract: The understanding of the functional role of aquatic bacteria in microbial food webs is largely dependent on methods applied to the direct visualization and enumeration of these organisms. While the ultrastructure of aquatic bacteria is still poorly known, routine observation of aquatic bacteria by light microscopy requires staining with fluorochromes, followed by filtration and direct counting on filter surfaces. Here, we used a new strategy to visualize and enumerate aquatic bacteria by light microscopy. By s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Our quantitative TEM analyses revealed a significant proportion of bacteria with a limiting capsule ( Figure 2B and 2Bi). Our data showed that 31 % of freshwater bacteria had capsular structures [20]. This frequency is higher than that found in marine bacteria (7-27 %) [21][22][23].…”
Section: A 3b 3bimentioning
confidence: 48%
See 4 more Smart Citations
“…Our quantitative TEM analyses revealed a significant proportion of bacteria with a limiting capsule ( Figure 2B and 2Bi). Our data showed that 31 % of freshwater bacteria had capsular structures [20]. This frequency is higher than that found in marine bacteria (7-27 %) [21][22][23].…”
Section: A 3b 3bimentioning
confidence: 48%
“…Our data from samples collected from Batata Lake suggest that OMV-mediated secretion is an important cell process of freshwater bacteria (Figure 3). Although the function of OMV remains to be defined, these secretory vesicles, observed for the first time by us in aquatic bacteria from a tropical ecosystem [20], may be important for bacterial survival and inhibition of lysis induced by viral infection that is relevant in this ecosystem [44], as mentioned before. Moreover, OMVs may be relevant in the transport of products involved in the formation of the cell wall, inhibition of toxic components present in the surrounding environment, and formation of biofilms.…”
Section: Production Of Outer Membrane Vesicles By Freshwater Bacteriamentioning
confidence: 71%
See 3 more Smart Citations